Phospholipase C Gamma - Carpenter, Graham; Crooke, Cornelia (Henry Stewart Talks, 2007)
PLC-gamma in growth factor signaling, PLC-gamma as an enzyme, Substrate and products, PLC family members, Domains, Association of PLC-gamma with activated receptor tyrosine kinases and membranes, Tyrosine phosphorylation sites of PLC-gamma, PLC-gamma1 verses PLC-gamma2, Measurement of protein and enzymatic activation, Downstream signaling by PLC-gamma in T cells, PLC-gamma mediation of integrins during adhesion and spreading, PLC-gamma biologic roles
Archived at 2018/05/31